Development Of E-Book For Learning Arabic Reading Skills Based On A Genre Based Approach For Senior High School Students - Ishak, Dina Mustika; Asrori, Imam; Nurhidayati, Nurhidayati (Ijaz Arabi Journal of Arabic Learning, 2025)
This research aims to describe the development of an e-book for learning Arabic reading skills based on a genre-based approach and the feasibility/validity of the developed e-book product. The research method used is research and development with the ADDIE model, which consists of five development steps, namely: 1) analysis, 2) design, 3) development, 4) implementation, and 5) evaluation. Data collection instruments include interviews and questionnaires (validation sheet). The data analysis techniques used are qualitative and quantitative. This e-book contains a collection of Islamic stories with different text genres containing text, images, audio, and hyperlinks to increase students' reading interest, facilitate their understanding of the texts presented, and support students' reading skills training. The product validation results from material experts obtained a score of 89% in the very good category. Meanwhile, validation from media experts obtained a score of 96% in the very good category. Based on the validation results, the e-book product for learning Arabic reading skills based on a genre-based approach is valid and can be implemented with students.